Endonasal skull base endoscopy - Simal-Julián, Juan Antonio; Miranda-Lloret, Pablo; Pancucci, Giovanni; Evangelista-Zamora, Rocío; Pérez-Borredá, Pedro; Sanromán-Álvarez, Pablo; Perez-de-Sanromán, Laila; Botella-Asunción, Carlos (Neurocirugía (Asturias, Spain), 2013)
The endoscopic endonasal techniques used in skull base surgery have evolved greatly in recent years. Our study objective was to perform a qualitative systematic review of the likewise systematic reviews in published English language literature, to examine the evidence and conclusions reached in these studies comparing transcranial and endoscopic approaches in skull base surgery. We searched the references on the MEDLINE and EMBASE electronic databases selecting the systematic reviews, meta-analyses and evidence based medicine reviews on skull based pathologies published from January 2000 until January 2013. We focused on endoscopic impact and on microsurgical and endoscopic technique comparisons. Full endoscopic endonasal approaches achieved gross total removal rates of craniopharyngiomas and chordomas higher than those for transcranial approaches. In anterior skull base meningiomas, complete resections were more frequently achieved after transcranial approaches, with a trend in favour of endoscopy with respect to visual prognosis. Endoscopic endonasal approaches minimised the postoperative complications after the treatment of cerebrospinal fluid (CSF) leaks, encephaloceles, meningoceles, craniopharyngiomas and chordomas, with the exception of postoperative CSF leaks. Randomized multicenter studies are necessary to resolve the controversy over endoscopic and microsurgical approaches in skull base surgery.